Literarni vidiki novomedijskih del Jake Železnikarja in Sreča Dragana - Bovcon, Narvika (Primerjalna književnost, 2013)
This paper presents examples of new media literature as found in the works of two Slovene new media artists: Jaka Železnikar and Srečo Dragan. Whereas Železnikar is primarily a net.artist that authors new media poetry and on-line linguistic interventions, the literary segments in Dragan's work are based on conceptual art and video art. Dragan employs their function to initiate a happening.
Keywords: Železnikar, Jaka, 1971-; Dragan, Srečo, 1944-; digitalna umetnost; digitalna književnost; novi mediji; kibertekst; interaktivna poezija; vizualna poezija